1991
DOI: 10.1152/ajplung.1991.261.2.l41
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoking induces an elastolytic cysteine proteinase in macrophages distinct from cathepsin L

Abstract: Degradation of the interstitium of the lung by elastolytic enzymes is thought to be a critical component of the pathogenesis of emphysema. Alveolar macrophages are increased in numbers in cigarette smokers and contain the elastolytic cysteine proteinase cathepsin L. We sought to determine if cigarette smoking induces a change in cathepsin L levels in alveolar macrophages which would, in turn, alter the expression of elastolytic activity. Lysates of smokers' macrophages, assayed at pH 5.50, degraded more than s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…This activity is reported to be elevated in BAL fluid as well as lysates of BAL cells from smokers [12], but other reports have suggested that the activity attributed to cysteine proteinases in BAL cell lysates may be due not only to cathepsin L but also to other cysteine proteinases [29]. As cathepsins S and K were recently discovered and reported to have an elastolytic activity, this may explain such undetermined activities in BAL cell lysates and/or in BAL fluid itself.…”
Section: Discussionmentioning
confidence: 95%
“…This activity is reported to be elevated in BAL fluid as well as lysates of BAL cells from smokers [12], but other reports have suggested that the activity attributed to cysteine proteinases in BAL cell lysates may be due not only to cathepsin L but also to other cysteine proteinases [29]. As cathepsins S and K were recently discovered and reported to have an elastolytic activity, this may explain such undetermined activities in BAL cell lysates and/or in BAL fluid itself.…”
Section: Discussionmentioning
confidence: 95%
“…Cigarette smoke and other irritants stimulate alveolar macrophages to produce MMPs [33,34] and cathepsins [35]. MMP1 degrades collagen whereas MMP9, MMP12, CTSL and CTSS degrade elastin [36].…”
Section: Discussionmentioning
confidence: 99%
“…Cathepsins B, L, and S all work at acidic pH and their proteolytic activity is neutralized at neutral pH with the exception of cathepsin S (12). Cathepsin L activity has been shown to be elevated in bronchoalveolar lavage (BAL) fluid from emphysema (13) and the release of cathepsin B and S from macrophages has been induced by cigarette smoking (14,15). Indeed, cathepsin L has been shown to cleave and inactivate ␣ 1 -antitrypsin (16), the major serine protease inhibitor present in the lung (17).…”
Section: Secretory Leucoprotease Inhibitor (Slpi)mentioning
confidence: 99%